STRATEGI PELESTARIAN STRUKTUR CAGAR BUDAYA MASJID RAYA PEKANBARU - Friska Jumnofri; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The structure of the Cultural Heritage of the Raya Pekanbaru Mosque from the rest of the old building of the mosque should be preserved. According to the Republic of Indonesia Law Number 11 of 2010 concerning Cultural Heritage, Preservation is a dynamic effort to maintain the existence of cultural heritage and its value by protecting, developing and utilizing it. Therefore, a strategy is needed that is carried out with an insightful vision and is intended for present and future interests. The purpose of this study was to determine the preservation of cultural heritage structures as well as to formulate a preservation strategy for the Raya mosque culture structure in Pekanbaru City. The research method used was descriptive qualitative which was then carried out strategy formulation using the SWOT analysis method. The results showed that the preservation of the cultural heritage structure in the Pekanbaru Raya Mosque that was carried out was still not maximal and had not yet achieved the expected goal, namely the lack of coordination between related agencies. It is better for the relevant offices to optimize socialization and improve supervision and procedures for preserving cultural preservation for the community or other stakeholders, so that there will be no more miscommunication, both cultural preservation in Pekanbaru City and in Riau Province.Kata Kunci: Strategy, Preservation, Cultural Heritage Structure